Temperature-Dependent Phenology Model for Encarsia tabacivora, a Parasitoid of Bemisia tabaci MEAM1 - Gamarra, H.; Carhuapoma, Pablo; Supanta, L.; Sporleder, M.; Kroschel, Jürgen (2025)
This report presents the first comprehensive temperature-dependent phenological model for Encarsia tabacivora, demonstrating that the parasitoid exhibits maximum population growth between 15 and 30 °C, with an optimum around 24–26 °C. The model, validated under fluctuating temperatures, constitutes a strategic tool for biological control and integrated pest management (IPM) programs, allowing for the optimization of mass rearing, release timing, and selection of suitable regions under current and future climate change scenarios. This work aligns strongly with Regenerative Agriculture, Resilient Agrifood Systems, and Climate-smart Agriculture.